Entrepreneurship education and self-efficacy among Chinese college students mediated by harmonious passion and moderated by parental psychological control - Yuan Gao; Jinjin Lu (Scientific Reports)
Abstract Despite the rapid development of entrepreneurship education among college students, limited research has examined the hindering role of Chinese parents in this process under the socio-cultural context of China. To address this gap, a quantitative study was conducted to investigate how entrepreneurship education enhances college students’ entrepreneurial self-efficacy (ESE) and the impact of Chinese parental psychological control (PPC). Data were collected from 1,411 college students using structured questionnaires and analyzed using hierarchical regression. Findings revealed that entrepreneurship education significantly boosts college students’ ESE, mediated by harmonious passion. Besides, PPC exerted a negative moderating effect, weakening the positive impact of entrepreneurship education on students’ ESE. This study enriches the understanding of the mechanisms underlying effective entrepreneurship education. It also offers practical implications for entrepreneurship education and training, business educators, and parenting practices in China.